INVESTIGATION OF PRECAUST PRESTRESSED SHELL - Zhiv, Alexander S.; Pershakov, Valery M.; Bilyk Alena О. (Proceedings of National Aviation University (archive), 2008)
The paper focuses on construction, production and erection of elements, methodology of testing and researching results of precaust prestressed shell from light concrete with dimensions 12×24m, which is used for covering of industrial building.